Perspektif Filsafat Pendidikan: Tantangan Implementasi Profil Pelajar Pancasila di Sekolah - Imam Subayil; Wayan Suastra; Muzakkir Walad; Ulyan Nasri (Al-Munawwarah : Jurnal Pendidikan Islam, 2024)
Education in Pancasila in Indonesia aims to shape the character of students in accordance with the values of Pancasila. The Pancasila Student Profile in schools is an initiative to measure the implementation of these values. The challenges of implementing the Pancasila student profile in schools are the focus of this qualitative research, involving literature reviews, participatory observations, and interviews. Data was collected through literature reviews, participatory observations, and in-depth interviews with teachers, students, and school staff. Thematic analysis revealed several challenges, including conceptual understanding constraints, resistance from students and teachers, and school policies that are not fully supportive. This research contributes to understanding the constraints and challenges of implementing the Pancasila Student Profile, with implications for formulating more effective education policies. The recommendations support the implementation of Pancasila values in primary and secondary education.